Human fetal adrenal cells retain age‐related stem‐ and endocrine‐differentiation potential in culture. Issue 2 (24th September 2018) - Poli, Giada; Sarchielli, Erica; Guasti, Daniele; Benvenuti, Susanna; Ballerini, Lara; Mazzanti, Benedetta; Armignacco, Roberta; Cantini, Giulia; Lulli, Matteo; Chortis, Vasileios; Arlt, Wiebke; Romagnoli, Paolo; et al.
ABSTRACT: The adrenal gland is a multiendocrine organ with a steroidogenic mesenchymal cortex and an inner catecholamine‐producing medulla of neuroendocrine origin. After embryonic development, this plastic organ undergoes a functional postnatal remodeling. Elucidating these complex processes is pivotal for understanding the early bases of functional endocrine disorders and tumors affecting the mature gland. We developed an in vitro human adrenal cell model derived from fetal adrenal specimens at different gestational ages, consisting of neuroendocrine and cortical components and expressing the zona and functional markers of the original fetal organ. These cortical and neuroendocrine progenitor cells retain in vitro an intrinsic gestational‐age–related differentiation and functional program. In vitro these cells spontaneously form 3‐dimensional structure organoids with a structure similar to the fetal gland. The organoids show morphofunctional features and adrenal steroidogenic factor, steroid acute regulatory, cytochrome‐P450‐17A1, dosage‐sensitive, sex‐reversal, adrenal hypoplasia–critical region on chromosome X protein, NOTCH1, and nephroblastoma overexpressed/cysteine‐rich protein 61/connective tissue growth factor/nephroblastoma overexpressed gene‐3; stem (BMI1, nestin); and chromaffin (chromogranin A, tyrosine hydroxylase) markers similar to those of the populations of origin. This in vitro human adrenal system represents a unique but preliminar model for investigating the pathophysiological processes underlying physiologic adrenal remodeling and pathologic alterations involved in organ hypo‐ and hyperplasia and cancer.—Poli, G., Sarchielli, E., Guasti, D., Benvenuti, S., Ballerini, L., Mazzanti, B., Armignacco, R., Cantini, G., Lulli, M., Chortis, V., Arlt, W., Romagnoli, P., Vannelli, G. B., Mannelli, M., Luconi, M. Human fetal adrenal cells retain age‐related stem‐and endocrine‐differentiation potential in culture. FASEB J. 33, 2263–2277 (2019). www.fasebj.org